Characterization of a Novel LUCAT1/miR-4316/VEGF-A Axis in Metastasis and Glycolysis of Lung Adenocarcinoma - Wang, Lishui; Xie, Yan; Wang, Jing; Zhang, Ying; Liu, Shibiao; Zhan, Yao; Zhao, Yinghui; Li, Juan; Li, Peilong; Wang, Chuanxin (Frontiers in Cell and Developmental Biology, 2022)
Objective: Accumulating literatures suggested that long non-coding RNAs (lncRNAs) were involved in tumorigenesis and cancer progression in lung adenocarcinoma (LUAD). However, the precise regulatory mechanism of lncRNA Lung cancer-associated transcript 1 (LUCAT1) in LUAD is not well defined. In this study, we aimed to investigate the biological function and mechanism of lncRNA LUCAT1 in regulating tumor migration and glycolysis of LUAD. Methods: High throughput sequencing was performed to identify differentially expressed lncRNAs between LUAD patients and healthy controls. The expression levels of LUCAT1 in LUAD clinical specimens or cell lines were evaluated by In situ hybridization (ISH) and quantitative Real-Time Polymerase Chain Reaction (qRT-PCR). Functional experiments, including wound-healing, transwell invasion assays, glucose absorption, lactate metabolism and tumor xenograft experiments were conducted to identify the biological functions of LUCAT1 in LUAD. Silencing of LUCAT1, over-expression of LUCAT1 and miR-4316 were generated in LUAD cell lines to verify the regulatory mode of LUCAT1-mir-4316-VEGFA axis. Results: Our findings revealed that lncRNA LUCAT1 was significantly up-regulated in LUAD serum exosomes, tumor tissues and LUAD cells in comparison with corresponding controls. Receiver operating characteristic curve (ROC) analysis indicated that the area under the curve (AUC) value of serum exosomal LUCAT1 reached 0.852 in distinguishing LUAD patients from healthy individuals. High expression of LUCAT1 in LUAD patient tissues was associated with enhanced Lymph Node Metastasis (LNM), advanced Tumor Node Metastasis (TNM) stage and poorer clinical outcome in LUAD patients. Knockdown of LUCAT1 inhibited LUAD cell metastasis and glycolysis in vitro as well as tumor metastasis in vivo, while overexpression of LUCAT1 induced a promoted LUAD metastasis and glycolysis. Furthermore, mechanistic investigations revealed that LUCAT1 elevated LUAD cell metastasis and glycolysis by sponging miR-4316, which further led to the upregulation of VEGFA. Finally, the regulatory axis LUCAT1-miR-4316-VEGFA was verified in LUAD. Conclusion: Our present research suggested that LUCAT1 facilitate LUAD cell metastasis and glycolysis via serving as a competing endogenous RNA to regulate miR-4316/VEGF-A axis, which provided a novel diagnostic marker and therapeutic target for LUAD patients.